The Inactive Participation of Parents as Governors at Schools for Learners with Special Education Needs - Premishwar Haripersad (International Journal of Advanced Science and Technology, 2020)
The need for this study arose from the author’s personal observation during his involvement in school governance that the majority of parents of disabled learners was losing interest in becoming members of school governing bodies (SGBs) in a democratised South Africa. It is apparent from this study as collaborated by other researchers that the prevailing system of governing LSEN schools is one of the significant factors that impede the decision-making process at schools thereby necessitating the need for remedial action to be taken by the relevant authorities.